2016
DOI: 10.1183/13993003.01369-2015
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of objective cough frequency in pulmonary sarcoidosis

Abstract: Cough is a common symptom of pulmonary sarcoidosis. This study aimed to quantify cough frequency, and investigate its relationship with cough reflex sensitivity, pulmonary function and health status.32 patients with pulmonary sarcoidosis were compared with 40 healthy controls. Cough reflex sensitivity to capsaicin, objective 24-h cough counts, cough-specific health status, cough severity and cough triggers were measured. The predictors of cough frequency in sarcoidosis were determined in a multivariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 40 publications
4
56
1
Order By: Relevance
“…We found no evidence of a diurnal pattern in aerosol Mtb production. While this might reflect a bias of hospitalisation disrupting natural diurnal rhythm, a diurnal pattern of cough pattern was observed that is concordant with other studies 10,11,13 . It is also interesting that 53 positive aerosol samples were collected from participants that were directly observed to be sleeping for the full hour of sampling.…”
Section: Discussionsupporting
confidence: 91%
“…We found no evidence of a diurnal pattern in aerosol Mtb production. While this might reflect a bias of hospitalisation disrupting natural diurnal rhythm, a diurnal pattern of cough pattern was observed that is concordant with other studies 10,11,13 . It is also interesting that 53 positive aerosol samples were collected from participants that were directly observed to be sleeping for the full hour of sampling.…”
Section: Discussionsupporting
confidence: 91%
“…Cough is frequently preceded by an urge-to-cough, a sensation of irritation or itching in the throat, which is also called laryngeal paresthesia 31. The frequency of allotussia or urge-to-cough varies according to population and methodology, but it is reported to occur in ~99% of these patients 23453132. Moreover, these characteristics of cough are similar to those of pain, such as allodynia, which is the pain caused by stimuli that do not normally provoke pain 28.…”
Section: Evidence For Neuropathology In Cough Hypersensitivity Syndromementioning
confidence: 99%
“…Furthermore, there was a significant association between the frequency of cough measured objectively with 24-h cough monitoring and health-related quality of life. In the study by Sinha et al, 9 cough reflex sensitivity assessed with capsaicin was the only independent predictor of the frequency of coughing. Lung function, disease activity, and severity were not predictors of cough frequency.…”
mentioning
confidence: 87%
“…[6][7][8] Cough is also a common symptom in patients with pulmonary sarcoidosis. A study by Sinha et al 9 reported that 50% of patients had a chronic cough and this was associated with poor health-related quality of life. Furthermore, there was a significant association between the frequency of cough measured objectively with 24-h cough monitoring and health-related quality of life.…”
mentioning
confidence: 99%